Understanding texts in early Judaism: studies on biblical, qumranic, deuterocanonical and cognate literature in memory of Géza Xeravits - Zsengellér, József (Deuterocanonical and cognate literature studies, 2022)
This volume remembers Géza Xeravits, a well known scholar of deuterocanonical and Qumran literature. The volume is divided into four sections according to his scholarly work and interest. Contributions in the first part deal with Old Testament and related issues (Thomas Hiecke, Stefan Beyerle, and Mattew Goff). The second section is about the Dead Sea Scrolls (John J, Collins, John Kampen, Peter Porzig, Eibert Tigchelaar, Balázs Tamási and Réka Esztári). The largest part is the forth on deuterocanonica (Beate Ego, Lucas Brum Teixteira, Fancis Macatangay, Tobias Nicklas, Maria Brutti, Nuria, Chalduch-Benages, Panc Beentjes, Ben Wright, Otto Mulder, Angelo Passaro, Friedrich Reiterer, Severino Bussino, Jeremy Corley and JiSeong Kwong). The third section deals with some cognate literature (József Zsengellér and Karin Schöpflin). The last section about the Ancient Synagogue has the paper of Anders Kloostergaard Petersen.Some hot topics are discussed, for example the Two spirits in Qumran, the cathegorization of the Dead Sea Scrolls, the authorship and antropology of Ben Sira, and the angelology of Vitae Prophetarum